Using Blade Element Momentum Theory to Predict the Effect of Wave-Current Interactions on the Performance of Tidal Stream Turbines. (March 2021) - Fu, Song; Ordonez-Sanchez, Stephanie; Martinez, Rodrigo; Allmark, Matthew; Johnstone, Cameron; O'Doherty, Tim
No abstract available